How users organize electronic files on their workstations in the office environment: a preliminary study of personal information organization behaviour - Christopher S.G. Khoo; Brendan Luyt; Caroline Ee; Jamila Osman; Hui-Hui Lim; Sally Yong (Information Research: An International Electronic Journal)
An ongoing study of how people organize their computer files and folders on the hard disk of their office workstations. A questionnaire was used to collect information on the subjects, their work responsibilities and characteristics of their workstations. Data on file and folder names and file structure were extracted from the hard disk using a computer program STG FolderPrint Plus, DOS command and screen capture. A semi-structured interview collected information on subjects' strategies in naming and organizing files and folders, and in locating and retrieving files. The data were analysed mainly through qualitative analysis and content analysis. The subjects organized their folders in a variety of structures, from broad and shallow to narrow and deep hierarchies. One to three levels of folders is common. The labels for first level folders tended to be task-based or project-based. Most subjects located files by browsing the folder structure, with searching used as a last resort. The most common types of folder names were document type, organizational function or structure, and miscellaneous or temporary. The frequency of folders of different types appear related to the type of occupation.